Disability and Quality Of Life among the Psychiatric Patients: A Cross-Sectional Hospital Based Study in Nepal - Shrestha, Barsha; Upadhaya, Saugat Keshari; Shrestha, Megha; Regmi, Saurav; Kunwar, Dipak; Risal, Ajay (Journal of Nobel Medical College, 2025)
Background: To study disability and quality of life within the psychiatric patients presenting to the Psychiatric out-patient unit at a University Hospital.Materials and Methods: It is a hospital based cross sectional study among the patient age group 18-65 years who presented to out-patient unit in Department of Psychiatry in a period of one year after ethical clearance from the institute. Participants were assessed by both validated Nepali versions tools: Disability assessment scale, World Health Organization Disability Assessment Schedule and World Health Organization Quality of Life 8-question scale (N=700). A structured questionnaire was used by the researchers that included personal and demographic characteristics and illness related parameters. The relationships between the variables, Disability, and quality of life were analyzed using independent sample t-tests.Results: Among 700 individuals presenting to the Psychiatric out-patient department and the disorders being categorized into 5 groups (Depressive disorders, Anxiety disorders, Somatoform disorders, Psychotic spectrum disorders, and Others), Anxiety disorders are the most common (49.6%) of cases to be diagnosed. Disability scores show a statistically significant difference (p=0.00), with females having higher disability scores than males. Individuals earning above five lakhs have significantly higher quality of life scores (p=0.00), suggesting a strong association between income and overall well-being.Conclusion: Gender and income show statistically significant relationships with quality of life and disability, whereas other factors exhibit minor variations without strong significance.